1983
DOI: 10.1113/jphysiol.1983.sp014851
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a chloride conductance activated by hyperpolarization in Aplysia neurones.

Abstract: SUMMARY1. A voltage-clamp study was made of some properties of the non-synaptic hyperpolarization-activated C1-conductance recently described in Aplysia neurones loaded with Cl-ions (Chesnoy-Marchais, 1982). The experiments were performed on an identified family of neurones, which present cholinergic responses allowing an easy measurement of the equilibrium potentials of Cl-(EC1) and K+ ions (EK).2. The Cl-selectivity ofthe hyperpolarization-activated conductance was deduced from four observations: (1) the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 45 publications
9
64
0
Order By: Relevance
“…More detailed studies of ClC_2, including measurements of ClC_2 expressed in smaller cells, are definitely necessary for a more profound understanding of its complex gating mechanisms. In several cell types, native hyperpolarization-activated Cl¦ currents that resemble ClC_2 strongly depend on [Cl¦]é (Chesnoy-Marchais, 1983;Dinudom et al 1993;Staley, 1994;Fritsch & Edelman, 1996;Ferroni et al 1997). Our findings support the hypothesis that these currents are indeed mediated by ClC_2.…”
Section: Discussionsupporting
confidence: 80%
“…More detailed studies of ClC_2, including measurements of ClC_2 expressed in smaller cells, are definitely necessary for a more profound understanding of its complex gating mechanisms. In several cell types, native hyperpolarization-activated Cl¦ currents that resemble ClC_2 strongly depend on [Cl¦]é (Chesnoy-Marchais, 1983;Dinudom et al 1993;Staley, 1994;Fritsch & Edelman, 1996;Ferroni et al 1997). Our findings support the hypothesis that these currents are indeed mediated by ClC_2.…”
Section: Discussionsupporting
confidence: 80%
“…Our data clearly prove that ClC-2 mediates a previously described chloride conductance (Chesnoy-Marchais, 1983;Madison et al, 1986;Smith et al, 1995) in CA1 pyramidal cells and a subset of interneurons. In addition to the absence of this conductance in Clcn2 Ϫ /Ϫ neurons, we observed the same biophysical properties Figure 6.…”
Section: Discussionsupporting
confidence: 59%
“…In the case of the channel studied here, the mean open-time sequence is Ca > Sr > Ba > Mg and the mean closed-time is also clearly dependent on the nature ofthe permeant ion, a property which has only been described for a few other channels (the opening rate constant seems to be ion dependent in the case of the anomalous K rectifier (Hagiwara et al 1976) and in the case of the Aplysia hyperpolarizationactivated Cl channel (Chesnoy-Marchais, 1983) In most cases where such a conclusion was proposed (see the above references), the substitution of permeant ions by other ions of identical valency did not affect the activation time constant by a factor larger than 2 or 3. In the present paper, it has been shown that the mean open-time can be affected by a factor of about 9 for the Ca-Ba substitution and by a factor of about 40 for the Ca-Mg substitution.…”
Section: Discussionmentioning
confidence: 96%
“…9B: the Ca and Ba curves might cross above +15 mV). (The idea that there could be differences between a 'permeability' sequence and a 'conductance' sequence had already been proposed earlier (see Hagiwara, Toyama & Hayashi, 1971;Hille, 1984 Van Helden, Hamill & Gage, 1977;Gage & Van Helden, 1979 for the frog muscle end-plate acetylcholine-activated cationic channel; Ascher, Marty &Neild, 1978 andMarty, 1979 for the Aplysia acetylcholine-activated cationic channel; Swenson & Armstrong, 1981 for the squid giant axon K current; Hagiwara, Miyazaki &Rosenthal, 1976 andHestrin, 1981 for the starfish egg and frog muscle K anomalous rectifier; Chesnoy- Marchais, 1983 for the Aplysia hyperpolarization-activated Cl current). In the case of Ca channels too, the activation kinetics have sometimes been considered as dependent on the nature of the permeant ion.…”
Section: Discussionmentioning
confidence: 99%